Interplay between Endoplasmic Reticulum Stress and Large Extracellular Vesicles (Microparticles) in Endothelial Cell Dysfunction - Aisha Osman; Tarek Benameur; Hesham M. Korashy; Asad Zeidan; Abdelali Agouni (Biomedicines, 2020)
Upon increased demand for protein synthesis, accumulation of misfolded and/or unfolded proteins within the endoplasmic reticulum (ER), a pro-survival response is activated termed unfolded protein response (UPR), aiming at restoring the proper function of the ER. Prolonged activation of the UPR leads, however, to ER stress, a cellular state that contributes to the pathogenesis of various chronic diseases including obesity and diabetes. ER stress response by itself can result in endothelial dysfunction, a hallmark of cardiovascular disease, through various cellular mechanisms including apoptosis, insulin resistance, inflammation and oxidative stress. Extracellular vesicles (EVs), particularly large EVs (lEVs) commonly referred to as microparticles (MPs), are membrane vesicles. They are considered as a fingerprint of their originating cells, carrying a variety of molecular components of their parent cells. lEVs are emerging as major contributors to endothelial cell dysfunction in various metabolic disease conditions. However, the mechanisms underpinning the role of lEVs in endothelial dysfunction are not fully elucidated. Recently, ER stress emerged as a bridging molecular link between lEVs and endothelial cell dysfunction. Therefore, in the current review, we summarized the roles of lEVs and ER stress in endothelial dysfunction and discussed the molecular crosstalk and relationship between ER stress and lEVs in endothelial dysfunction.